On the histogenesis of mixed germ cell-sex cord stromal tumour of the gonads. Issue 3 (25th July 2016) - Roth, Lawrence M; Cheng, Liang
Abstract : Aims: The origin of testicular mixed germ cell-sex cord stromal tumour (MGC-SCST) is uncertain, and the nature of this neoplasm is controversial. It has not been established whether the germ cells in testicular MGC-SCST are neoplastic or whether they are merely entrapped within an unclassified sex cord stromal tumour or related testicular neoplasm. In this investigation, we present additional evidence regarding the nature of the germ cells in testicular MGC-SCST. Methods: We obtained 25 cases of MGC-SCST, 13 of which involved the testis and 12 occurred in the ovary for histological examination. Although the majority of the cases studied were archival, materials were available for immunocytochemical examination in 10 instances. Results: We found that 10 of 13 testicular MGC-SCSTs studied had a sex cord component resembling unclassified sex cord stromal tumour. In two MGC-SCSTs that had prominent entrapped tubules, an intratubular component was identified. A total of 12 ovarian MGC-SCSTs were examined, and these neoplasms were more diverse in their histological appearance than the testicular examples. The germ cells often resembled those of dysgerminoma. Formation of imperfect follicular-like structures was a frequent feature in ovarian cases. Conclusions: In this investigation, we provide further evidence that the germ cells in testicular MGC-SCSTs are neoplastic; however, in the great majority of tumours, these cells are low-grade. Some testicular MGC-SCSTs arise from an intratubular component. We believe that the majority of ovarian and some testicular MGC-SCSTs arise more directly from simultaneous transformation of germ cells and sex cord derivatives.